Innovation and Utilization of Functional Feed Additives from Maize By-Products in Broiler Chickens - Orranee Srinual; Chanidapha Kanmanee; Phatchari Srinual; Thanongsak Chaiyaso; Mongkol Yachai; Tanya Tapingkae; Wanaporn Tapingkae (Animals)
Supplementation with spent mushroom substrate (SMS) as an exogenous enzyme in broiler diets represents a promising nutritional strategy to enhance production efficiency and reduce costs. To assess the effects of SMS enzyme products on various parameters, including growth performance, blood chemistry, carcass and meat quality, and gut health, a study was conducted with one-day-old broilers (n = 500). The broilers were separated into five groups: a control diet (CON) and an antibiotic group (AGP) which were added to the diet at 0.25 g kg−1, and SMS from Flammulina velutipes supplementation groups which were added to the diet at 0.5 g kg−1 (SMS0.5), 1.0 g kg−1 (SMS1.0), and 2.0 g kg−1 (SMS2.0). Final body weight and average daily gain in broilers which were fed the AGP diet were higher than in broilers which were fed the CON, SMS0.5, and SMS1.0 diets. Broilers in the CON group had a decreased average daily feed intake compared to other groups. The addition of AGP and SMS2.0 diets improved the feed conversion ratio and reduced the feed cost per gain in broilers. Broilers that were fed the CON diet had the highest serum cholesterol, while the AGP diet increased triglyceride. Dietary supplementation of SMS improved some carcass characteristics and ceacum microbial content in broilers, especially with the SMS2.0 diet. Broiler fed CON and SMS0.5 worsened the villus height/crypt depth ratio of duodenum histology. In conclusion, SMS supplementation at 1.0 and 2.0 g kg−1 can improve productive performance and health in broiler diets; however, SMS2.0 had the best efficiency.